2005
DOI: 10.1021/bm050380m
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Conjugates of Carbon Nanotubes and DNA by a Solid-State Reaction

Abstract: DNA-wrapped nanotubes of both multiwalled and single-walled carbon nanotubes were obtained by a solid-state mechanochemical reaction. Scanning electron microscopic images show that the nanotubes were cut into shorter lengths and were fully covered with DNA, which was further confirmed by fluorescence microscopy. This resulted in a high aqueous solubility of the products with a stability of >6 months. The results show that nanotubes were cut also with uniform distribution where >90% of the multiwalled products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…[21][22][23][24] Our research group has long been involved in the study of CNTs [25,26] and we have recently reported a novel and simple route to obtain supramolecular adducts [27] of CNT-DNA conjugates from both MWNTs and SWNTs based on a novel solid-state mechanochemical reaction. [28] In an earlier report we have also shown a rapid purification [29] and individualization [30] /dispersion [31] techniques for SWNTs. Motivated by these approaches introduced in our laboratory in association with our extensive experience with polymeric materials, [25,27,32,33] we attempted to expand this idea to the solubilization or dispersion of SWNTs with polymers, in turn facilitating the preparation of SWNT-polymer composites.…”
Section: Introductionmentioning
confidence: 91%
“…[21][22][23][24] Our research group has long been involved in the study of CNTs [25,26] and we have recently reported a novel and simple route to obtain supramolecular adducts [27] of CNT-DNA conjugates from both MWNTs and SWNTs based on a novel solid-state mechanochemical reaction. [28] In an earlier report we have also shown a rapid purification [29] and individualization [30] /dispersion [31] techniques for SWNTs. Motivated by these approaches introduced in our laboratory in association with our extensive experience with polymeric materials, [25,27,32,33] we attempted to expand this idea to the solubilization or dispersion of SWNTs with polymers, in turn facilitating the preparation of SWNT-polymer composites.…”
Section: Introductionmentioning
confidence: 91%
“…All these processes are caused only by the mechanical impact on the mixture of solid reagents. Previously, several stress-induced mechanochemical reactions of solid materials and organic reagents without solvent and heating have been reported [9][10][11][12][13][14]. However, as far as we know, this technique has rarely been applied on cellulose modification.…”
Section: Introductionmentioning
confidence: 99%
“…p-p interactions between the CNT sidewalls and the nucleic acid bases have been proposed as the mechanistic basis for this wrapping effect. Moreover, the ability of DNA to wrap around the CNT surface has been described for both double-stranded DNA [226,227] and single-stranded DNA [91], and has been utilized to disperse CNTs in solvents of varying polarity.…”
Section: 71mentioning
confidence: 99%